Metabolic Profiling of Inga Species with Antitumor Activity - Lima, Nerilson M. [UNESP]; Preet, Gagan; Marqui, Sara R. [UNESP]; Falcoski, Thaís de O. R. S. [UNESP]; Navegante, Geovana [UNESP]; Soares, Christiane P. [UNESP]; Andrade, Teresinha de Jesus A. S.; La Porta, Felipe A.; Rakotondraie, Harinantenaina Liva R.; Jaspars, Marcel; Silva, Dulce H. S. [UNESP] (MDPI, 2022)
This work evaluated the metabolic profiling of Inga species with antitumor potential. In addition, we described the antigenotoxicity of polyphenols isolated from I. laurina and a proteomic approach using HepG2 cells after treatment with these metabolites. The in vitro cytotoxic activity against HepG2, HT-29 and T98G cancer cell lines was investigated. The assessment of genotoxic damage was carried out through the comet assay. The ethanolic extract from I. laurina seeds was subjected to bioassay-guided fractionation and the most active fractions were characterized. One bioactive fraction with high cytotoxicity against HT-29 human colon cancer cells (IC50 = 4.0 µg mL−1) was found, and it was characterized as a mixture of p-hydroxybenzoic acid and 4-vinyl-phenol. The I. edulis fruit peel (IC50 = 18.6 µg mL−1) and I. laurina seed (IC50 = 15.2 µg mL−1) extracts had cytotoxic activity against the cell line T98G, and its chemical composition showed a variety of phenolic acids. The chemical composition of this species indicated a wide variety of aromatic acids, flavonoids, tannins, and carotenoids. The high concentration (ranging from 5% to 30%) of these polyphenols in the bioactive extract may be responsible for the antitumor potential. Regarding the proteomic approach, we detected proteins directly related to the elimination of ROS, DNA repair, expression of tumor proteins, and apoptosis.
Keywords: antigenotoxicity; bioactive polyphenols; cytotoxicity; metabolomic; proteomic; reactive oxygen species